Do L1 Chinese speakers use melodic strategies to convey sadness and joy in L2 Spanish? A melodic analysis of speech of L2 acted emotional speech - Sun, Shaohua; Herrero-Fernández, Cristina (Círculo de Lingüística Aplicada a la Comunicación, 2025)
Little research has been carried out on L2 acted emotional speech, either from the production or from the perceptual point of view (Pellegrino and Maffia, 2016), which may be due to the widespread acceptance of the theory that states that a second language is less emotional for the late learner than the L1 (Harris, 2004). Whether this emotional distance is due to the lack of emotion in the contexts where a second language is acquired (Ivaz et al., 2016) or not, the communicative competence of L2 speakers also depends on their ability to convey the emotions they intend to convey when communicating in L2. Several authors have recently studied the specific acoustic cues of L1 Spanish emotional speech and therefore underlined the vital role of prosody (Garrido Almiñana, 2011; Hidalgo, 2020; Padilla, 2020). At the same time, other researchers have suggested that L1 paralinguistic intonation patterns and cultures may influence how L2 emotional speech is produced and perceived (Chen, 2005; De Abreu and Mathon, 2005; De Marco, 2019). Also, it has been scientifically proven that poor production and perception of emotional speech can lead to misinterpretations and cause serious misunderstandings in intercultural communication (Holden and Hogan, 1993). However, there is a gap in the field of L2 Spanish research regarding the perception and production of emotional speech. The present study aims to fill this gap and investigate whether Chinese speakers of L2 Spanish living in Spain use any melodic strategy to try to convey sadness and joy. For this purpose, a corpus of 100 pairs of utterances produced by Chinese speakers of L2 Spanish living in Spain to convey sadness and joy was elicited and analyzed using the Melodic Analysis of Speech (Cantero and Font-Rotchés, 2020). The pairs of utterances were characterized by having the same lexical content and by only differing by the communicative intention of the speaker. The study’s results shed light on whether Chinese L2 Spanish speakers use melodic strategies to convey different emotions (joy and sadness) in L2 or not.